PERAN INTELLECTUAL CAPITAL TERHADAP IMPLEMENTASI NEW PUBLIC MANAGEMENT DALAM PENINGKATAN KINERJA MANAJERIAL SEKTOR PUBLIK - Lili Indrawati (Jurusan Akuntansi Politeknik Negeri Bandung, 2016)
Abstract: The purpose of this research is to analyze and prove the role of intellectual capital against implementation of new public management in enhancing public sector managerial performance. The research was carried out at the Cimahi local government. The number of respondent was 258 employees from 42 working units. The research method used is purposive sampling. To analyze the data from the respondent is interaction regression. The research shows that intellectual capital does not affect the relationship between NPM and public sector managerial performance. Keywords: New Public Management, Intellectual Capital and Performance of Public Sector Managerial, Cimahi Local Government